2010
DOI: 10.1007/s00395-010-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M-enhanced vascular endothelial growth factor expression in human vascular smooth muscle cells involves PI3K-, p38 MAPK-, Erk1/2- and STAT1/STAT3-dependent pathways and is attenuated by interferon-γ

Abstract: The pleiotropic cytokine oncostatin M (OSM), a member of the glycoprotein (gp)130 ligand family, plays a key role in inflammation and cardiovascular disease. As inflammation precedes and accompanies pathological angiogenesis, we investigated the effect of OSM and other gp130 ligands on vascular endothelial growth factor (VEGF) production in human vascular smooth muscle cells (SMC). Human coronary artery SMC (HCASMC) and human aortic SMC (HASMC) were treated with different gp130 ligands. VEGF protein was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…Various studies have reported that several stimuli, including IFN-γ and TNF-α, can also activate the extracellular signal-regulated kinase (ERK), p38 MAPK, and NF-κB pathways. [30][31][32] Under normal conditions, NF-κB combines with inhibitor of kappa B-α (IκB-α) in the cytoplasm. IFN-γ and TNF-α, among other cytokines, can induce the phosphorylation and degradation of IκB-α, leading to the subsequent phosphorylation of NF-κB and its translocation into the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported that several stimuli, including IFN-γ and TNF-α, can also activate the extracellular signal-regulated kinase (ERK), p38 MAPK, and NF-κB pathways. [30][31][32] Under normal conditions, NF-κB combines with inhibitor of kappa B-α (IκB-α) in the cytoplasm. IFN-γ and TNF-α, among other cytokines, can induce the phosphorylation and degradation of IκB-α, leading to the subsequent phosphorylation of NF-κB and its translocation into the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…OSM has been known to activate the JAK/ STAT in many kinds of cells (Gomez-Lechon 1999). According to several records, OSM induces JAK1 and JAK2 phosphorylation and activation of STAT2 and STAT3 in vascular smooth muscle cells, and in vascular smooth muscle JAK3 was activated by OSM signaling pathway (Bernard et al 1999;Nagata et al 2003;Demyanets et al 2011). Furthermore, OSM can activate JAK2, JAK3, and stimulate the osteogenic differentiation of human adipose mesenchymal stem cells (hADSCs), increase the expression of osteogenic differentiation markers, such as ALP, RUNX2, osteocalcin and so on (Song et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Correlates with VSMC Synthetic Phenotype-Previous studies have shown that VEGF is a key regulator of physiological and pathological angiogenesis, which inhibits VSMC apoptosis and promotes VSMC proliferation by suppressing the expression of VSMC marker genes (34,35). Our data revealed that although the STAT3 mRNA level in HAVSMCs was not significantly changed after incubating with 50 ng/ml VEGF for different time periods (12,24, and 48 h), the phosphorylated (p)-STAT3 protein expression was significantly elevated to 3-6-fold compared with control levels (Fig.…”
Section: Activated Stat3mentioning
confidence: 99%